Proposed model of oral health program for primary schools in region one provinces. - กัลยาสิริ, เกษม; ชัยพฤกษ์, ศรีโรจน์ (Thai Dental Public Health Journal, 2008)
This study aims to propose the model of oral health programme for primary schools in health area region one, the data were collected through questionnaires, randomly in dept interviews of the school's administrators and health teachers during May - August 2004. Thirty-two schools responded the questionnaires and six schools responded the interviews. The results showed that the dental health surveillance activities remained in all schools but lacked of effective monitoring and evaluation. Majorities of schools integrated oral health learning in the area of health and physical education. Dental personnel show an obvious role in the participation to develop student oral health while local administration's role was apparent. All schools were adapting their management and learning method to the Basic Education Curriculum 2001. The situational analysis and the information from the related documents about new curriculum, the innovated self evaluation of oral health suggest the proposal of multisector co-operation model that, Public Health sector should render technical support and dental health services in school. Educational sector should be responsible in oral health environment and learning both in the curriculum and the student development activity, particularly the tooth brushing lessons that evaluate the development of the student's oral health. Local Administration and the community should allocate the resources enable to promote dental health of the students.